MEK1/2 Inhibition in Murine Heart and Aorta After Oral Administration of Refametinib Supplemented Drinking Water - Steijns, Felke; Bracke, Nathalie; Renard, Marjolijn; De Backer, Julie; Sips, Patrick; Debunne, Nathan; Wynendaele, Evelien; Verbeke, Frederick; De Spiegeleer, Bart; Campens, Laurence (Frontiers in Pharmacology, 2020)
Upregulation of the RAS-RAF-MEK-ERK-MAPK pathway is involved in the development of several human tumors, aortic aneurysms, atherosclerosis and cardiomyopathy. Refametinib, a highly selective MEK-inhibitor, has already shown antineoplastic activity in phase II trials. Furthermore, it showed potency to attenuate aortic root growth in murine models. Current formulations of this drug however necessitate oral gavage as a delivery method for long-term studies, which is labor-intensive and induces stress and occasional injury, potentially confounding results. Therefore, we developed a novel oral administration method for refametinib. A 2-hydroxypropyl-beta-cyclodextrin (HPBCD) based drinking water preparation of refametinib was formulated, for which a selective, analytical UHPLC-UV method was developed to assess the in-use stability. Next, 16 week old male wild-type C57Bl/6J mice received either a daily dose of 50 or 75 mg/kg/day refametinib (n = 16 or 12, respectively) or were given regular drinking water during 7 days (n = 4) after which refametinib plasma levels were measured. Subsequently, mice receiving a daily dose of 50 mg/kg/day refametinib and untreated mice were sacrificed after which pERK/total ERK protein levels were calculated in the myocardial and aortic tissue (n = 4/group). After 7 days no significant degradation of refametinib was observed when dissolved in drinking water provided that drinking bottles were protected from UV/visible light. Furthermore, a dose-dependent increase in refametinib plasma levels was found whereby active plasma levels (>1.2µg/ml) were obtained even in the lowest dose-group of 50 mg/kg/day. A significant reduction of pERK/total ERK protein levels compared to untreated mice was observed in aortic and myocardial tissue of mice receiving a daily dose of 50 mg/kg/day refametinib. Importantly, a relatively high mortality rate was noted in the highest dose group (n = 5). This approach provides a valid alternative oral administration method for refametinib with a reduced risk of complications due to animal manipulation and without loss of functionality, which can be implemented in future research regarding the malignant upregulation of the RAS-RAF-MEK-ERK-MAPK pathway. However, care must be taken not to exceed the toxic dose.